2015
DOI: 10.1584/jpestics.d15-045
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactones are transported from roots to shoots, although not through the xylem

Abstract: Strigolactones (SLs) mainly produced in roots move upward to shoots and inhibit axillary bud outgrowth. However, SLs were not detected by LC-MS/MS in xylem saps collected from rice, tomato, cucumber, tobacco, sorghum, and Arabidopsis. d 1 -Orobanchol and d 6 -4-deoxyorobanchol that were fed to roots of rice plants were detected in shoots harvested 20 hr after treatment, although not in the xylem sap. These results imply that both endogenous and exogenous SLs are transported from roots to shoots, although not t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…SLs in the harvested shoot tissues were extracted and analyzed by LC-MS/MS as described previously. 7) These stereoisomers were detected with the same or with very similar sensitivities in the LC-MS/MS analyses conducted in the present study. The separation of SL stereoisomers with chiral LC-MS/ MS was essentially the same as that reported previously.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…SLs in the harvested shoot tissues were extracted and analyzed by LC-MS/MS as described previously. 7) These stereoisomers were detected with the same or with very similar sensitivities in the LC-MS/MS analyses conducted in the present study. The separation of SL stereoisomers with chiral LC-MS/ MS was essentially the same as that reported previously.…”
supporting
confidence: 77%
“…In our previous report, we demonstrated that root-applied SLs are transported to shoots, although not through the xylem. 7) In the present study, we examined whether this root-to-shoot transport was dependent on the structure and/or stereochemistry of SLs in rice (orobanchol-type SL producer), sorghum (strigol-type SL producer), and tobacco (producing both types).…”
Section: -3)mentioning
confidence: 99%
See 1 more Smart Citation
“…The SLs were detected in shoots harvested 20 hr after but not 2 hr after treatment. 53) These results strongly suggest that exogenous and endogenous SLs are transported from roots to shoots not through the xylem but through hypodermal passage cells as in Petunia where polar and asymmetric localization of an ABC transporter (PaPDR1) have been shown to mediate shootward SL transport as well as localized exudation into the rhizosphere. 54,55) Furthermore, aforementioned species-specific phenomena in SL production also occur in the transport of exogenous SLs from the roots to shoots, indicating that the transport is structure-and stereospecific.…”
Section: Transport Of Sls From Roots To Shootsmentioning
confidence: 76%
“…We collected large amounts of xylem sap from various plant species including tomato and Arabidopsis but no signals attributable to known canonical or non-canonical SLs were detected by LC-MS/MS analyses. 53) Then, deuterated SLs, d 1 -orobanchol and d 6 -4DO, were fed to roots of rice plants and the shoots were harvested 2 and 20 hr after SL treatment. The SLs were detected in shoots harvested 20 hr after but not 2 hr after treatment.…”
Section: Transport Of Sls From Roots To Shootsmentioning
confidence: 99%